2012
DOI: 10.1111/jph.12059
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, Purification and Initial Analysis of a Novel Pectate Lyase Pcpel1 from Phytophthora capsici

Abstract: Phytophthora capsici inflicts damage on numerous crop plants by secreting a series of pectinase including pectate lyase (PEL). Here, we report a pectate lyase gene (Pcpel1) from a genomic library of a highly virulent P. capsici strain SD33. Pcpel1 was identified as an open reading frame of 1233 bp encoding a protein of 410 amino acids with a predicted amino-terminal signal sequence of 21 amino acids. The predicted protein of Pcpel1 has a calculated molecular mass of 43.8 kDa and a pI value of 6.8. Analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Alignment of P. parasitica full-length PL1 proteins showed that they have a number of conserved residues, with pairwise identity ranging from 21% to 100%. Two PL1 proteins from P. capsici, Pcpel1 and Pcpel2 [NCBI: FJ213434, FJ213435] have been identified as pectate lyases, having activity against unesterified polygalacturonic acid (PGA) [ 120 , 121 ]. Pcpel2 has 74-90% amino acid identity with three P. parasitica PL1s [PPTG_12901, 12902 and 20388] while Pcpel1 has 87% identity with one P. parasitica PL1 [PPTG_18908], suggesting that these P. parasitica proteins will act on unesterified HG.…”
Section: Resultsmentioning
confidence: 99%
“…Alignment of P. parasitica full-length PL1 proteins showed that they have a number of conserved residues, with pairwise identity ranging from 21% to 100%. Two PL1 proteins from P. capsici, Pcpel1 and Pcpel2 [NCBI: FJ213434, FJ213435] have been identified as pectate lyases, having activity against unesterified polygalacturonic acid (PGA) [ 120 , 121 ]. Pcpel2 has 74-90% amino acid identity with three P. parasitica PL1s [PPTG_12901, 12902 and 20388] while Pcpel1 has 87% identity with one P. parasitica PL1 [PPTG_18908], suggesting that these P. parasitica proteins will act on unesterified HG.…”
Section: Resultsmentioning
confidence: 99%
“…They cleave the glycosidic bonds of two saccharide units via a β-elimination mechanism ( Collmer and Keen, 1986 ; Herron et al, 2000 ). Studies have shown that pectate lyases contribute to virulence of bacteria, fungi, nematodes, and oomycetes ( Wegener, 2002 ; Fu et al, 2013 ; Cho et al, 2015 ; Chen et al, 2021 ). A study of pectate lyase genes PL1 , PL15 , PL16 , and PL20 from P. capsici showed that overexpression of these genes in a mildly virulent strain transformed it to a highly aggressive strain ( Fu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pel A gene from Aspergillus nidulans has been successfully expressed in Bacillus subtilis [99] and E. coli [100]. Pectate lyase gene designated as Pcpel2 and Pcpel1from Phytophthora capsicin have been cloned and expressed in E. coli and Pichia pastoris respectively [101,102] revealing its significant role in pathogenesis. The open reading frame of Pcpel1I gene is 1233 bp and encodes 410 amino acid polypeptide, including 21 residues long amino terminal signal sequence.…”
Section: Fungal Pectate Lyasesmentioning
confidence: 99%